2005
DOI: 10.1111/j.1468-5906.2005.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Attitudes Toward Physician‐Assisted Suicide and Terminal Palliative Care

Abstract: We assess religious differences in attitudes toward physician-assisted suicide and terminal palliative care, and go further than previous research by attempting to explain these variations. Using data from the 1998 General Social Survey, we fit OLS regression models to estimate the main effects of religious affiliation and indirect effects via religious involvement (church attendance and strength of affiliation). Both conservative and moderate Protestants are generally less accepting of physician-assisted suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 44 publications
(73 reference statements)
8
74
0
2
Order By: Relevance
“…Because many people see these as moral issues, much of the research in this area has focused on the role of religion. For example, several studies address the effect of religion on suicide ideology (DeCesare, 2000;Monte, 1991;Sawyer and Sobol, 1987;Seidlitz et al, 1995;Singh, 1979;Wasserman, 1992, 1995;Stack et al, 1994), as well as on attitudes toward euthanasia and physician-assisted suicide (Adams et al, 1978;Anderson and Caddell, 1993;Bachman et al, 1996;Burdette et al, 2005;DeCesare, 2000;Hamil-Luker and Smith, 1998;Holden, 1993;Klopfer and Price, 1978-79;Leinbach, 1993;MacDonald, 1998;Monte, 1991;Seale and Addington-Hall, 1994;Seidlitz et al, 1995;Singh, 1979). Results from these studies generally demonstrate that religion plays a key role in shaping positions on these issues.…”
Section: Introductionmentioning
confidence: 89%
“…Because many people see these as moral issues, much of the research in this area has focused on the role of religion. For example, several studies address the effect of religion on suicide ideology (DeCesare, 2000;Monte, 1991;Sawyer and Sobol, 1987;Seidlitz et al, 1995;Singh, 1979;Wasserman, 1992, 1995;Stack et al, 1994), as well as on attitudes toward euthanasia and physician-assisted suicide (Adams et al, 1978;Anderson and Caddell, 1993;Bachman et al, 1996;Burdette et al, 2005;DeCesare, 2000;Hamil-Luker and Smith, 1998;Holden, 1993;Klopfer and Price, 1978-79;Leinbach, 1993;MacDonald, 1998;Monte, 1991;Seale and Addington-Hall, 1994;Seidlitz et al, 1995;Singh, 1979). Results from these studies generally demonstrate that religion plays a key role in shaping positions on these issues.…”
Section: Introductionmentioning
confidence: 89%
“…They also found that being younger and/or Black significantly influenced disapproval of euthanasia. Burdette et al (2005) found that conservative Protestants were significantly different than were liberal Protestants and other faiths in opposing PAS. Burdette et al also found that African Americans were less accepting of PAS.…”
Section: End-of-life Decisionsmentioning
confidence: 96%
“…He may cry for rest, peace, and dignity, but he will get infusions, transfusions, a heart machine, or tracheotomy if necessary.- Kubler-Ross, 1969, p. 22 According to Burdette, Hill, and Moulton (2005) and Emery and Pargament (2004), religious concerns may be particularly important at the end of life, because it may have an impact on decisions regarding medical treatments. Religious and spiritual beliefs can affect decisions around prolonging life, do-not-resuscitate (DNR) instructions, hospice and palliative care, and physicianassisted suicide (PAS).…”
Section: End-of-life Decisionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Yet euthanasia for adults remains an extremely controversial subject and views tend to correlate with religious affiliation and race [37,38]. For example, in 2014, Quebec legalized euthanasia for competent adults with its Act Respecting End-of-Life Care [39], spurring Canada's parliament to pass legislation legalizing euthanasia for adults in June 2016 [40].…”
Section: North American Contextmentioning
confidence: 99%